Informal Economy and Peacebuilding Efforts among Muslim and Christian Communities during Communal Conflicts in Ambon - Abellia Anggi Wardani (Islamica: Jurnal Studi Keislaman, 2021)
Communal conflicts that happened in Ambon, eastern part of Indonesia more than 20 years ago still reserve a lot of lessons to unveil. One of the least discussed issues is the roles of economic exchanges among diverse community members in bringing peace from below. This article tries to capture the interreligious interactions (Muslim and Christian) among buyers and sellers in areas considered as border space during the conflicts from 1999 to 2004. It showcases the intertwin of everyday peacebuilding efforts through trade and the spread of peace messages among those involved in the exchange practices. This research employed qualitative research methods using ethnographic strategy with in-depth interview, observation, and library study. Data was collected from 2016-2019 including 10-month intensive fieldwork. The article discusses that social networks and cultural ties embedded in the economic drivers of trade-related activities arguably set the foundation for everyday peacebuilding. In conclusion, economic transactions allowed interethnic, intervillage, and interreligious interactions to take place, eliminated distrust among the traders, and potentially extended peace message narratives at the micro level such as among family members.